Platelet Transfusion Thresholds: How Low Can We Go in Respect to Platelet Counting? - Lippi, Giuseppe; Favaloro, Emmanuel J.; Buoro, Sabrina (Seminars in Thrombosis and Hemostasis, 2020)
Platelet transfusion is conventionally used to prevent or treat bleeding in patients with low platelet counts or impaired platelet function. The identification of accurate thresholds of platelet count for guiding platelet transfusion practices is a crucial aspect in health care to prevent adverse events, side effects, unwarranted costs for the health care service, and deprivation of supplies. This article is therefore aimed at providing a narrative overview on current guidelines and recommendations for platelet transfusion across many clinical settings, including platelet function disorders, and critically analyzing the available platelet transfusion thresholds according to the current analytical performance of platelet counting with automated hematological analyzers. Overall, universal agreement on the definition of platelet transfusion thresholds has not been reached. The degree of accuracy and imprecision of many fully automated hematological analyzers appears also unsatisfactory, especially at the lower thrombocytopenic range, and this may thus jeopardize the managed care of patients who are candidates for platelet transfusions. Potential solutions to overcome the current shortcomings of automated platelet counting are also discussed, encompassing the use of alternative tests for guiding platelet transfusion (e.g., thrombin generation assays or thromboelastography) along with innovative approaches for platelet enumeration (e.g., fluorescent labeling and flow cytometry).
Keywords: platelets; transfusion; bleeding; imprecision; inaccuracy